Neonatal Anthropometric Measures and Peripherally Inserted Central Catheter Depth. (August 2021) - Armbruster, Debra; Slaughter, Jonathan; Stenger, Michael; Warren, Patrick
Abstract : Background: Peripherally inserted central catheters (PICCs) are used routinely in neonatal care. Measures of surface anatomy have been used to estimate appropriate PICC depth in neonates since 1973. However, prior PICC research using anthropometric measures to estimate proper PICC insertion depth has been limited to pediatric and adult literature. Purpose: The purpose of this study was to explore the relationships among a neonate's anthropometric measures and the appropriate PICC insertion depth. Methods: Neonates requiring PICC insertion at Nationwide Children's Hospital were enrolled between January and September 2018. Standard PICC procedures were followed. The research group corroborated appropriate PICC tip position of enrolled infants. Multivariable linear regression with robust standard errors was used to evaluate linear relationships between PICC insertion depth and current weight, current length, and PICC insertion site. Results: Demographics of enrolled infants included gestational ages of 23 to 39 weeks, weights of 510 to 3870 g, and lengths of 31 to 54 cm. Of the 56 infants considered, final statistical analysis included 49 neonates (14 ankle, 16 knee, and 19 antecubital insertions). Current neonatal weight was associated with PICC depth at all sites (all P s < .0001). Current neonatal length was associated with PICC depth at all sites (all P s < .0001). Preprocedure surface measurement was also strongly associated with PICC insertion depth ( P < .0001). Implications for Practice: This investigation demonstrated a relationship for both neonatal weight and length that may be an anthropometric model for neonatal PICC insertion depth. Implications for Research: A more robust sample size could more precisely define the anthropometric model.